Clinical Research on Delayed Cure after Microvascular Decompression for Hemifacial Spasm - Li, Ming-Wu; Jiang, Xiao-Feng; Wu, Min; He, Fang; Niu, Chaoshi (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2020)
Objective The clinical data of patients with hemifacial spasm (HFS) were analyzed statistically to identify factors leading to delayed cure after microvascular decompression (MVD).Methods A retrospective analysis of the clinical data of 600 patients with HFS subjected to MVD from March 2016 to May 2018 was performed. Student t test, chi-square test, logistic regression analysis, and multivariate analysis of variance were used to analyze the correlation between delayed cure and its related factors.Results Among the 600 patients enrolled, 117 had delayed cure after MVD. The shortest duration of delayed cure was 4 days, and the longest was 540 days, with an average of 108 days. The frequency of delayed improvement in these patients was not associated with sex, age, or offending vessel type (p > 0.05); however, delayed cure was positively correlated with the course of the disease, grade of HFS severity, and disappearance of abnormal muscle responses during the operation (p < 0.05). Moreover, a longer disease course was associated with more severe related symptoms and a longer duration of postoperative delayed cure.Conclusion MVD is an effective treatment for HFS. Given that postoperative delayed cure was unavoidable, even with accurate identification of the offending vessel and sufficient decompression of the root exit zone, delayed cure should be considered in patients undergoing reoperation due to lack of remission or relapse after the operation. Additionally, the timing of efficacy assessments should be delayed.
Keywords: hemifacial spasm; microvascular decompression; delayed cure